Radiological response of primary central nervous system lymphoma after corticosteroid therapy and its predictive value on overall survival: a multicenter study - Florian Scheichel; D. Pinggera; T. Rossmann; B. Popadic; S. Aspalter; V. Schön; A. Woehrer; M. M. Dorostkar; C. Dorfer; C. F. Freyschlag; F. Marhold (Journal of Neuro-Oncology, 2026)
Abstract Background Primary Large-B-Cell Lymphoma of the CNS (PCNS-LBCL) is a rare, aggressive tumor often sensitive to corticosteroid therapy (CST). This multicenter study investigated the spectrum of radiological responses to routine CST and evaluated its impact on patient prognosis. Methods The researchers utilized a prospective cohort of 18 patients for volumetric MRI analysis and a combined prospective-retrospective cohort of 31 patients for 2D tumor analysis. Patients received CST post-biopsy, with follow-up MRIs performed on the seventh day (median) after surgery. The study correlated radiological responses with CST dosage, LDH levels, and overall survival (OS) using Kaplan-Meier and Firth-corrected Cox regression. Results In the prospective cohort, 83.3% of tumors regressed with a median regression of 40%, while 16.7% progressed despite CST resulting in a median progression of 46%. These changes were not dose-dependent, but there were indications of a correlation with LDH levels. Patients showing regression had a median OS of 31.4 months, compared to 3.9 months for tumors progressing during CST ( p = 0.015). Firth-corrected Cox regression showed, despite the small sample size, that radiological response ( p = 0.02) could be a promising prognostic factor in a model including age, type of therapy and Karnofsky performance status. Conclusion This study provides the first structured description of the range of radiological responses of PCNS-LBCL to CST. Furthermore, we found exploratory indications that radiological response to CST may predict outcome indicating shared sensitivity to other cytotoxic drugs. Further studies are necessary to fully understand diagnostic and prognostic implications of CST sensitivity in PCNS-LBCL and its underlying mechanisms.